2011
DOI: 10.1007/s00421-011-2205-8
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in neuromuscular function after a 5 km running time trial

Abstract: The aim of this study was to characterize the effect of a 5 km running time trial on the neuromuscular properties of the plantar flexors. Eleven well-trained triathletes performed a series of neuromuscular tests before and immediately after the run on a 200 m indoor track. Muscle activation (twitch interpolation) and normalized EMG activity were assessed during maximal voluntary contraction (MVC) of plantar flexors. Maximal soleus H-reflexes and M-waves were evoked at rest (i.e. H (MAX) and M (MAX), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…In this study, strength losses in PF were relatively modest (~9 %) as compared to the losses induced by running exercises (~10–40 %; Girard et al 2012; Millet et al 2011; Perrey et al 2010; Racinais et al 2007) but were in accordance with the losses previously observed after a maximal cycling exercise (~8 %; Racinais and Girard 2012). Maximal EMG activity and twitch interpolation recordings obtained during MVC were used to assess the completeness of plantar flexors activation capacity.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, strength losses in PF were relatively modest (~9 %) as compared to the losses induced by running exercises (~10–40 %; Girard et al 2012; Millet et al 2011; Perrey et al 2010; Racinais et al 2007) but were in accordance with the losses previously observed after a maximal cycling exercise (~8 %; Racinais and Girard 2012). Maximal EMG activity and twitch interpolation recordings obtained during MVC were used to assess the completeness of plantar flexors activation capacity.…”
Section: Discussionsupporting
confidence: 89%
“…The present study found that PF fatigue induced by a football game is rather modest as evidenced by a nonsignificant reduction of ∼ 5% in MVC torque ∼30 min post game, which was restored near baseline after 24 h. Quite similar acute (∼7% reduction in MVC torque) and delayed (full recovery within 24 h) alterations in maximal torque production capacity of the same muscle group have been described after playing tennis for ∼2 h in temperate conditions (Périard et al., ). Larger reductions (ranging 10%–30%) in PF MVC torque have been documented after prolonged, moderate‐intensity treadmill tasks (60–90 min: Racinais et al., ; Kelly et al., ) and shorter runs performed at high (5‐km race: Girard et al., ) or maximal intensity (repeated‐sprint ability test: Perrey et al., ). In football, the fact that PF are not particularly prone to fatigue compared with other muscle group such as the quadriceps (Nédélec et al., ) after competitive games would suggest that PF torque production capacity impairments may only have a limited impact on running pattern or involvement with the ball as fatigue develops.…”
Section: Discussionmentioning
confidence: 99%
“…Endurance performance involves the prolonged maintenance of constant or self-regulated power/velocity (e.g., Girard et al, 2012; Jones et al, 2016; Smits et al, 2016) or torque/force (e.g., Froyd et al, 2013; Pageaux et al, 2015a; Angius et al, 2016). Traditionally, endurance performance is measured by completion of time to exhaustion tests (i.e., open loop exercises) or time trials (i.e., closed loop exercises).…”
Section: Introductionmentioning
confidence: 99%